2016
DOI: 10.1002/ejhf.657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liraglutide, a glucagon‐like peptide‐1 analogue, on left ventricular function in stable chronic heart failure patients with and without diabetes (LIVE)—a multicentre, double‐blind, randomised, placebo‐controlled trial

Abstract: Aims To determine the effect of the glucagon‐like peptide‐1 analogue liraglutide on left ventricular function in chronic heart failure patients with and without type 2 diabetes. Methods and results LIVE was an investigator‐initiated, randomised, double‐blinded, placebo‐controlled multicentre trial. Patients (n = 241) with reduced left ventricular ejection fraction (LVEF ≤45%) were recruited (February 2012 to August 2015). Patients were clinically stable and on optimal heart failure treatment. Intervention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
263
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(314 citation statements)
references
References 33 publications
7
263
3
8
Order By: Relevance
“…Reassuringly, no heart failure-related adverse outcomes were detected in studies examining the safety of GLP-1R agonists in the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA), LEADER, Trial to Evaluate Cardiovascular and Other Long-term Outcomes With Semaglutide in Subjects With Type 2 Diabetes (SUSTAIN-6), or EXSCEL (18-21), which collectively enrolled thousands of subjects with mild to moderate heart failure. Nevertheless, three smaller dedicated studies of more advanced heart failure, two with liraglutide (24 weeks) and one with albiglutide (12 weeks), failed to demonstrate functional improvement in human subjects, with or without T2D, with reduced ejection fraction and a history of hospitalization for heart failure (59,63,64). Indeed, rehospitalization for heart failure was numerically more common with liraglutide (63), and increased reports of arrhythmias, including supraventricular tachycardia, were noted in liraglutide-treated subjects in these trials (63,64), consistent with the localization of GLP-1R expression to the sinoatrial node.…”
Section: Heart Failurementioning
confidence: 99%
“…Reassuringly, no heart failure-related adverse outcomes were detected in studies examining the safety of GLP-1R agonists in the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA), LEADER, Trial to Evaluate Cardiovascular and Other Long-term Outcomes With Semaglutide in Subjects With Type 2 Diabetes (SUSTAIN-6), or EXSCEL (18-21), which collectively enrolled thousands of subjects with mild to moderate heart failure. Nevertheless, three smaller dedicated studies of more advanced heart failure, two with liraglutide (24 weeks) and one with albiglutide (12 weeks), failed to demonstrate functional improvement in human subjects, with or without T2D, with reduced ejection fraction and a history of hospitalization for heart failure (59,63,64). Indeed, rehospitalization for heart failure was numerically more common with liraglutide (63), and increased reports of arrhythmias, including supraventricular tachycardia, were noted in liraglutide-treated subjects in these trials (63,64), consistent with the localization of GLP-1R expression to the sinoatrial node.…”
Section: Heart Failurementioning
confidence: 99%
“…In the liraglutide on left ventricular function (LIVE) trial, liraglutide did improve diastolic function as indicated by E/e′ in participants with an EF of <45% 20. Liraglutide might not improve cardiac function in an advanced stage but in moderate to mild impairment of cardiac function was improved.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have investigated the effects of liraglutide on cardiac function in patients with or without diabetes, and with either coronary heart disease (with preserved LVEF) [40][41][42] or CHF and reduced LVEF (< 40%) [43][44][45]. The results were widely heterogeneous.…”
Section: Effects Of Liraglutide On Cardiac Function and Cardiovasculamentioning
confidence: 99%
“…Indeed, three studies reported a significant increase in LVEF in patients with preserved LVEF [40,41] and reduced LVEF [43], whereas three other studies -one in patients with preserved cardiac function [42] and two in patients with altered function [44,45] -reported almost no changes in LVEF with liraglutide compared with a placebo (Table 3). The two largest trials, with follow-ups of about 6 months, also reported virtually no changes in LVEF [44,45]. Thus, it may be concluded that the effect of liraglutide on LVEF is, if anything, modest and probably not clinically relevant.…”
Section: Effects Of Liraglutide On Cardiac Function and Cardiovasculamentioning
confidence: 99%